2019
DOI: 10.1007/s10722-019-00770-0
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure in Fennoscandian landrace rye (Secale cereale L.) spanning 350 years

Abstract: Rye (Secale cereale L.) was for centuries the economically most important crop in Fennoscandia (Denmark, Finland, Norway and Sweden). Historical records tell of a range of different types adapted to climate and varying cultivation practices. Genetic analyses of genebank maintained landrace rye have yet failed, with a few exceptions, to detect differentiation between rye types. Concerns have been raised that genebank material does not truly reflect the historical variation in landrace rye. In this study, we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…Regarding the grain varieties being cultivated, current evidence suggest they were similar or of the same group of varieties grown in more northerly and cold latitudes. For example in regards to rye, Larsson et al(2019) found through genetic analysis of preserved Fennoscandian rye seeds that they all belonged to the same meta-population of rye landraces that had been stable for at least the last 350 years. Similarly, Aslan et al (2015) found that barley landraces from Fennoscandia form a homogenous group of barley landraces, distinct from other parts of Europe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the grain varieties being cultivated, current evidence suggest they were similar or of the same group of varieties grown in more northerly and cold latitudes. For example in regards to rye, Larsson et al(2019) found through genetic analysis of preserved Fennoscandian rye seeds that they all belonged to the same meta-population of rye landraces that had been stable for at least the last 350 years. Similarly, Aslan et al (2015) found that barley landraces from Fennoscandia form a homogenous group of barley landraces, distinct from other parts of Europe.…”
Section: Discussionmentioning
confidence: 99%
“…In a broader context of European rye landraces in the pre-1900 period, Fennoscandian landraces have been found in genomic studies to belong to a particular and separate meta-population of rye landraces, distinct from landraces in continental Europe. Furthermore, even southern Scandinavian rye landraces have been found to have more in common genetically with landraces from northeastern Europe rather than those from maritime western Europe (Larsson et al, 2019).…”
Section: Grain Cropsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, studies by Persson and van Bothmer [22] and Hagenblad et al [8] showed that some landraces can be distinguished geographically and that the clusters might reflect routes of migration and contact. Examples of clusters are the Finnmarken area (which is well known for slash-and burn cultivation of rye; see [23]) and Scotland and Morocco (argued to reflect seed exchange). Studies of historical museum and herbarium specimens of rye by Larsson et al [23] have confirmed the clustering of the Fennoscandian meta-population, but have not been able to illuminate a finer geographical distinction between different landraces within the Fennoscandian region.…”
Section: Insights Into Rye Domesticationmentioning
confidence: 99%
“…Historical specimens from museum or other institutional collections are valuable sources of information representing organisms that may be difficult or impossible to sample in contemporary populations (Holmes et al., 2016). Most studies that use historical specimens for phylogenetic reconstruction tend to focus on larger‐bodied species that are recently extinct (Anmarkrud & Lifjeld, 2017; Bunce et al., 2009; Mitchell et al., 2014; Sharko et al., 2019), well‐studied groups (Billerman & Walsh, 2019; Jarvis et al., 2014) and organisms of economic importance (Bonanomi et al., 2014; Larson et al., 2007; Larsson et al., 2019). Only recently have we begun to see an increase in such reports on invertebrate and other small‐bodied taxa (e.g., Cruaud et al., 2019; Der Sarkissian et al., 2017; Kistenich et al., 2019; Sproul & Maddison, 2017).…”
Section: Introductionmentioning
confidence: 99%